Propriedades estruturais e eletrônicas de nanotubos de carbono não convencionais - Silva, Paloma Vieira da (2020)
In this thesis, the structural and electronic properties of a set of nonconventional carbon nanotubes were studied through computational simulations. The calculations are based on Density Functional Theory (DFT) as implemented in the SIESTA package. A class of these nanotubes, called C60NTs, were built from fullerene-based sheets rolled-up along different directions. It was shown that their electronic properties closely follow those of their 2D counterparts, namely, tubes derived from type 1 (type 2) sheet are always metallic (semiconducting). These results are rationalized in terms of a zone folding approach. The influence of a transversal electric field on the properties of C60NTs was also investigated. It was observed that all families of NTs undergo radial deformation, but this is significantly stronger for large tubes. Regarding the electronic behavior, while the C60NT1s maintain the metallic character of the type 1 sheet, the C60NT2s undergo a transition from semiconductor to metal for certain values of the electric field dependending on the diameter. The second class of studied NTs were α-graphyne nanotubes. Initially, the properties of double-walled α-graphyne nanotubes (α-DWGNTs) with zig-zag chirality were investigated. It has been demonstrated that van der Waals interactions between layers significantly influence the stability of these nanostructures. Regarding the electronic properties, these interactions sligthly reduce the bang gap and hybridize the states of both tubes. As a consequence, the α-DWGNTs present specific sets of van Hove singularities, specially for the frontier states. Then, it was studied the radial deformation and collapse in single-walled α-graphyne nanotubes (α-SWGNTs)(n, n). The results show that the collapsed α-SWGNTs undergo a transition from metal to semiconductor when the diameter is ≥ 19 Å, with band gap depending on the stacking configuration. In addition to the investigation of nanotubes, three 2D carbon systems constructed out of acepentalene building blocks were studied. In all these structures, called tripentaphenes (TPHs), there is a resonance mechanism which accounts for the distribution of bond lengths. All TPHs are metallic and can act as good electron injectors. For these TPHs structures, the approximate energy bands of the corresponding NTs were calculated using the ZF method. The results found for C60NTs, α-DWGNTs, collapsed α-SWGNTs and TPHs present a series of properties that can enable their future use in electronic nanodevices.